A review of cleft lip and palate management: Experience of a Nigerian Teaching Hospital - Akinwale Adeyemi Efunkoya; Kelvin Uchenna Omeje; Ibiyinka Olushola Amole; Otasowie Daniel Osunde; Izegboya Olohitae Akpasa (African Journal of Paediatric Surgery, 2015)
Background: Cleft lip (CL) and palate (CLP) management is multidisciplinary. A cleft team was formed in a Nigerian Tertiary Hospital to address the health needs of cleft patients in the centre. Aim: This paper aims at documenting the Aminu Kano Teaching Hospital (AKTH) management protocol for orofacial clefts and also to review our experience with CLP surgeries performed at AKTH since our partnering with Smile Train. Materials and Methods: A retrospective review of all the cleft patients surgically treated from January 2006 to December 2014 under Smile Train sponsorship was undertaken. A descriptive narrative of the cleft team protocol was also given. Results: One hundred and fifty-five patients (80 males, 75 females) had surgical repairs of either the lip or palate. CL patients were 83 (53.55%), while CLP patients were 45 (29.03%) and isolated cleft palate patients were 27 (17.42%). Conclusion: The inclusion of various specialities in the cleft team is highly desirable. Poverty level amongst our patients frequently limits our management to surgical treatment sponsored by the Smile Train, despite the presence of other residual problems.